2011
DOI: 10.25011/cim.v34i6.15899
|View full text |Cite
|
Sign up to set email alerts
|

Plasma vitamin D levels and risk of metabolic syndrome in Canadians

Abstract: Purpose: Vitamin D deficiency has been implicated in susceptibility to the development of metabolic syndrome, obesity and type 2 diabetes mellitus. The present study aimed to quantify the association between vitamin D plasma level, the number of metabolic syndrome components and insulin resistance in Canadians. Methods: Vitamin D plasma level and clinical data were determined from 1,818 subjects from the Canadian Health Measures Survey; a representative health survey of the general population of Canada condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 23 publications
7
52
1
1
Order By: Relevance
“…proposition is supported by our recent findings that increasing plasma vitamin D level by 10 nmol/l was significantly inversely associated with HOMA-IR (p = 0.006) and results in 14% lower probability of having metabolic syndrome, a major risk factor in T2DM (CI = 0.75-0.99) [23]. To our knowledge, there are no long-term studies (≥ 6 months) examining the effects of higher vitamin D doses (≥ 4000 IU/day) on 2 hr post-challenge glucose, insulin sensitivity and secretion, disposition index, "omics"-based inflammatory markers and markers of hepatic steatosis in pre-diabetic subjects with vitamin D deficiency.…”
Section: Vitamin D In the Prevention Of T2dm: Clinical Trialssupporting
confidence: 75%
See 4 more Smart Citations
“…proposition is supported by our recent findings that increasing plasma vitamin D level by 10 nmol/l was significantly inversely associated with HOMA-IR (p = 0.006) and results in 14% lower probability of having metabolic syndrome, a major risk factor in T2DM (CI = 0.75-0.99) [23]. To our knowledge, there are no long-term studies (≥ 6 months) examining the effects of higher vitamin D doses (≥ 4000 IU/day) on 2 hr post-challenge glucose, insulin sensitivity and secretion, disposition index, "omics"-based inflammatory markers and markers of hepatic steatosis in pre-diabetic subjects with vitamin D deficiency.…”
Section: Vitamin D In the Prevention Of T2dm: Clinical Trialssupporting
confidence: 75%
“…Data from the Third National Health and Nutrition Examination Survey (NHANES III) showed that serum 25(OH)D was inversely associated with T2DM and HOMA-IR [54]. We have also reported an inverse association between vitamin D serum levels and HOMA-IR in a population of non-diabetic adults [23]. This inverse association suggests that 25(OH)D may play a role in decreasing insulin resistance upon sufficiency.…”
Section: Vitamin D Inflammation and T2dmsupporting
confidence: 51%
See 3 more Smart Citations